A mechano-driven multi-ion sensor based on piezo- ionophoretic coupling for real time perspiration monitoring. (December 2022) - KS, Abisegapriyan; Alluri, Nagamalleswara Rao; Sharma, Kusum; Maria Joseph Raj, Nirmal Prashanth; Kim, Sang-Jae
Highlights: A Mechano-driven ion selective (MDIS) sensor for perspiration monitoring was developed. Ionophore Crosslinked PANI (ICP) contributes to the excellent selectivity toward specific ions. The MDIS sensor components operate through the piezoelectric-iontophoretic coupling. MDIS performs well with artificial ions in the lab environment and on athletes (during perspiration in real time. Abstract: Studying various electrolyte concentrations in body fluid plays a vital role in health monitoring. Presently body fluids are not explored well in health monitoring. At the same time, it consists of many biomarkers, including electrolytes, metabolite-proteins, antigens, and cytokines which can play an essential role in health monitoring. Inadequate material and unreliable power supply methods restrict its applications. In this work, a fully flexible Mechano-Driven Ion-Selective (MDIS) perspiration sensor was fabricated from a highly electroactive β-PVDF with a simple phase inversion method to address these issues. The prepared PVDF-based piezoelectric nanogenerator, attached on medical adhesive tape, gives an electrical output of ∼2.5 V and ∼10 nA under bending conditions and acts as the power source. The MDIS consists of an ionophores cross-linked polymer (ICP) that acts as a sensor for selective detection of ions in perspiration. This sensor quantitatively analyses potassium, and sodium contents in perspiration to the sensitivities of 0.024 mM −1, and 0.059 mM −1, respectively. The MDIS perspiration sensor response varied as a function of the concentration of the ions. This mechano-driven biosensor with enhanced stability, flexibility, sensitivity, and selectivity furnishes real-time monitoring of ion concentration levels during perspiration. Graphical abstract: Image, graphical abstract